![](/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
Bài 2:
a: \(A=a^2+b^2+c^2+2ab-2ac-2bc+a^2+b^2+c^2-2ab-2bc+2ac\)
\(=2a^2+2b^2+2c^2-4bc\)
\(=2+2\cdot9+2\cdot1-4\cdot3\cdot\left(-1\right)=22+12=34\)
b: \(B=\left(a+b-a+b\right)\left(a+b+a-b\right)=4ab=4\cdot2\cdot5=40\)
![](/images/avt/0.png?1311)
a) Sửa đề: \(8x^3+36x^2+54x+27\)
Ta có: \(8x^3+36x^2+54x+27\)
\(=\left(2x\right)^3+3\cdot\left(2x\right)^2\cdot3+3\cdot2x\cdot3^2+3^3\)
\(=\left(2x+3\right)^3\)
b) Ta có: \(x^2+4x+4\)
\(=x^2+2\cdot x\cdot2+2^2\)
\(=\left(x+2\right)^2\)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
a, x2-x+1/4=(x-1/2)2
b, (x+1)3
c,(2x+1)3
d, (2-3x03
e, (10x)2-(x2+25)2=:[10x+(x2+25)][10x-(x2+25)]=(10x+x2+25)(10x-x2-25)
![](/images/avt/0.png?1311)
Tại x = 103/2 ta có :
\(M=5.\left(\dfrac{103}{2}\right)^3-36.\left(\dfrac{103}{2}\right)^2+54.\dfrac{103}{2}+27=590281,375\)
![](/images/avt/0.png?1311)
a. \(7x-x^2-6=0\)
\(\Rightarrow-x^2+7x-6=0\)
\(\Rightarrow-x^2+x+6x-6=0\)
\(\Rightarrow-x\left(x-1\right)+6\left(x-1\right)=0\)
\(\Rightarrow\left(x-1\right)\left(-x+6\right)=0\)
+) Nếu \(x-1=0\Rightarrow x=1\)
+) Nếu \(-x+6=0\Rightarrow x=6\)
Vậy x=1 hoặc x=6
b. \(8x^3-36x^2+57x-27=0\)
\(\Rightarrow\left(2x\right)^2-3.2^2.x^2.3+3.2x.3^2-3^3=0\)
\(\Rightarrow\left(2x-3\right)^3=0\)
\(\Rightarrow2x-3=0\Rightarrow x=\frac{3}{2}\)
Vậy...........
![](/images/avt/0.png?1311)
Bài 1:
b: \(=\left(x^2+x+4\right)^2+3x\left(x^2+x+4\right)+5x\left(x^2+x+4\right)+15x^2\)
\(=\left(x^2+x+4+3x\right)\left(x^2+x+4+5x\right)\)
\(=\left(x^2+4x+4\right)\left(x^2+6x+4\right)\)
\(=\left(x+2\right)^2\cdot\left(x^2+6x+4\right)\)
c: \(=25x^2-49y^2-\left(5x+7y\right)\)
\(=\left(5x-7y\right)\left(5x+7y\right)-\left(5x+7y\right)\)
\(=\left(5x+7y\right)\left(5x-7y-1\right)\)
d: \(8x^3-36x^2+54x-27=\left(2x-3\right)^3\)
![](/images/avt/0.png?1311)
![](/images/avt/0.png?1311)
a ) \(\left(x+2\right)^3-\left(x-2\right)^3\)
\(=\left[\left(x+2\right)-\left(x-2\right)\right]\left[\left(x+2\right)^2+\left(x+2\right)\left(x-2\right)+\left(x-2\right)^2\right]\)
8x3 - 36x2 + 54x - 26 = 0
8x3 - 8x2 - 28x2 + 28x + 26x - 26 = 0
8x2(x - 1) - 28x(x - 1) + 26(x - 1) = 0
(x - 1)(8x2 - 28x + 26) = 0
x - 1 = 0 hoặc 8x2 - 28x + 26 = 0
TH1: x - 1 = 0
x = 1
TH2: 8x2 - 28x + 26 = 0 (vô nghiệm)
Vậy x = 1